Social Egg Freezing in Islamic Law: Conditional Permissibility through a Maqāṣid al-Sharī‘ah and Gender Justice Perspective - Ridha Aulia; Ilzam Hubby Dzikrillah Alfani; Muhammad Ruhiyat Haririe; Denny Iswanto; Neng Hannah (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
This study analyzes the practice of social egg freezing for unmarried women from the perspective of Islamic law and its relevance to maqāṣid al-sharī'ah and gender justice. The phenomenon of modernity has led Muslim women to delay marriage and pregnancy for education and careers, creating tension between professional demands and biological reproductive limitations. This qualitative research employs a library-based method with a normative-theological approach, integrating tafsir, maqāṣid al-sharī'ah, qiyās, and sadd al-dharī'ah. Data were obtained from primary sources including Qur'anic verses, classical and contemporary tafsir works, and authoritative fatwas, supported by modern scientific literature. The findings indicate that social egg freezing can be understood as a form of human agency (ikhtiyar) to preserve reproductive potential while responding to the social realities of modern women. Legally, this practice falls within the framework of the "Conditional Permissibility Doctrine" (al-ibāḥah al-muqayyadah), namely conditional permissibility prioritizing lineage protection (ḥifẓ al-nasl). This permissibility requires use only within a valid marriage, prohibition of donation and surrogacy, medical safety guarantees, and control of lineage mixing risks. From a maqāṣid perspective, this practice relates to the protection of lineage, intellect (ḥifẓ al-'aql), property (ḥifẓ al-māl), and human dignity. Thus, social egg freezing can be positioned as a preventive and adaptive instrument of maṣlaḥah. This study affirms that Islamic law possesses methodological flexibility to respond to biotechnological developments justly and contextually, while strengthening women's position as autonomous legal subjects without disregarding Sharia principles.